Accessibility of Worship in Mosques for People with Disabilities - Kahfi, Muhammad Ashabul; Jamaluddin, Fitriani (Jayapangus Press, 2025)
People with disabilities often face challenges in fulfilling their rights, including the right to worship in mosques. This research aims to investigate the worship accessibility for people with disabilities in the Tana Luwu area and the role of religious mosque authorities in supporting the fulfillment of the religious rights of people with disabilities in Tana Luwu. This is qualitative research with case study approach, where the researcher interviewed five individuals with disabilities and three mosque authorities. Additionally, the researcher observed several mosques and collected relevant documentation. The research results show that people with disabilities in Tana Luwu face difficulties in accessing mosques in the area due to the lack of disability-friendly facilities. However, the absence of disability-friendly mosque facilities can be overcome with positive attention from mosque authorities and Jemaah or congregants. In general, physical barriers do not pose a significant obstacle for people with disabilities to worship because of the social support they receive from the surrounding community. Discussions about the religious rights of people with disabilities should be expanded, and real improvements in mosques are needed to make them inclusive places of worship.